Ubiquitination-Dependent Regulation of Small GTPases in Membrane Trafficking: From Cell Biology to Human Diseases - Lei, Zehui; Wang, Jing; Zhang, Lingqiang; Liu, Cui Hua (Frontiers in Cell and Developmental Biology, 2021)
Membrane trafficking is critical for cellular homeostasis, which is mainly carried out by small GTPases, a class of proteins functioning in vesicle budding, transport, tethering and fusion processes. The accurate and organized membrane trafficking relies on the proper regulation of small GTPases, which involves the conversion between GTP- and GDP-bound small GTPases mediated by guanine nucleotide exchange factors (GEFs) and GTPase-activating proteins (GAPs). Emerging evidence indicates that post-translational modifications (PTMs) of small GTPases, especially ubiquitination, play an important role in the spatio-temporal regulation of small GTPases, and the dysregulation of small GTPase ubiquitination can result in multiple human diseases. In this review, we introduce small GTPases-mediated membrane trafficking pathways and the biological processes of ubiquitination-dependent regulation of small GTPases, including the regulation of small GTPase stability, activity and localization. We then discuss the dysregulation of small GTPase ubiquitination and the associated human membrane trafficking-related diseases, focusing on the neurological diseases and infections. An in-depth understanding of the molecular mechanisms by which ubiquitination regulates small GTPases can provide novel insights into the membrane trafficking process, which knowledge is valuable for the development of more effective and specific therapeutics for membrane trafficking-related human diseases.